Autophagic Degradation of Misfolded Nuclear Receptor Co-repressor (NCoR) Is Linked to the Growth of Tumor Cells in HBX Positive Hepatocellular Carcinoma (HCC) - Tan, Su Yin; Visvanathan, Sridevi; Abu Hassan, Radzi; Khan, Matiullah (Frontiers in Oncology, 2019)
Hepatitis B virus (HBV) is causally linked to hepatocellular injury and cell death, which are followed by hepatocellular carcinoma (HCC) after a long latent period. The HBV derived X protein (HBX) is the most potent carcinogenic factor for HCC, however, the molecular mechanism of HBX-induced transformation of hepatic cells in HCC is poorly understood. We have shown that nuclear receptor co-repressor (NCoR) is essential for the spatial repression of global transcription by the promyelocytic leukemia oncogenic domains (PODs), a frequent target of viral oncoproteins like HBX and that disintegration of PODs due to misfolded conformation dependent loss (MCDL) of NCoR is linked to promyelocytic and monocytic acute myeloid leukemia (AML). Given the key role of NCoR in cellular homeostasis across various tissue subtypes, we hypothesized that HBX-induced MCDL of NCoR might be linked to HCC through similar mechanism. Based on this hypothesis, the conformation of NCoR in HCC derived tumor cells and primary human tissue sections were analyzed and a selective MCDL of NCoR in HBX positive HCC cells was identified. HBX triggered the misfolding of NCoR through ubiquitination, followed by its degradation by autophagy, thus suggesting a cross talk between ubiquitin proteasome system (UPS) and autophagy lysosomal pathway (ALP) in MCDL of NCoR in HBX positive HCC cells. SiRNA-induced NCoR ablation selectively impaired the growth and survival of HBX positive HCC cells, suggesting a role of MCDL in the growth and survival of HBX positive HCC cells. These finding identify a possible crosstalk between UPS and ALP in the misfolding and loss of NCoR in HBX positive HCC cells and suggest a role of autophagic recycling of misfolded NCoR in the activation of oncogenic metabolic signaling in HCC. The misfolded NCoR reported in this study represents a novel conformation based molecular target which could be valuable in the design and development of tumour cell specific diagnostic and therapeutic approach for HBX positive HCC.